Using indigenous artefacts to support conceptual field approach of learning special trigonometric angles - Ali, Clement Ayarebilla (Journal of Mathematics and Science Teacher, 2023)
Concerns have been expressed on the abstract nature of teaching and learning trigonometry in pre-tertiary institutions. However, studies on student-teachers mathematics learning shows that this concern could be ameliorated by using indigenous artefacts to support conceptual fields of trigonometry. With pre-/post design, the researcher selected 50 student-teachers through simple random sampling and performed experiments using indigenous artefacts in teaching and learning of 30o-60o-90o and 45o-45o-90o special trigonometry angles. This cohort has had at least two years of teaching experience in their permanent schools of work. After going through the experiments, two diagnostic tests (pre- and post-test) were administered, scored and analyzed with the SPSS software. The results of the descriptive statistics, one sample t-test, paired samples t-tests, and correlation coefficients showed that the student-teachers’ performance had significantly improved. The improvements were really attributable to the deployment of the indigenous artefacts to carry out the instruction in the special trigonometric angles. We, therefore, recommended that stakeholders should adopt indigenous artefacts to support the conceptual field approach for the teaching and learning of basic trigonometry.